Functional interaction of hybrid response elements with wild-type and mutant steroid hormone receptors. - Truss, M (1991)
Steroid hormone receptors can be divided into two subfamilies according to the structure of their DNA binding domains and the nucleotide sequences which they recognize. The glucocorticoid receptor and the progesterone receptor (PR) recognize an imperfect palindrome (glucocorticoid responsive element/progesterone responsive element [GRE/PRE]) with the conserved half-sequence TGTYCY, whereas the estrogen receptor (ER) recognizes a palindrome (estrogen responsive element) with the half-sequence TGACC. A series of symmetric and asymmetric variants of these hormone responsive elements (HREs) have been tested for receptor binding and for the ability to mediate induction in vivo. High-resolution analysis demonstrates that the overall number and distribution of contacts with the N-7 position of guanines and with the phosphate backbone of various HREs are quite similar for PR and ER. However, PR and glucocorticoid receptor, but not ER, are able to contact the 5'-methyl group of thymines found in position 3 of HREs, as shown by potassium permanganate interference. The ER mutant HE84, which contains a single amino acid exchange, Glu-203 to Gly, in the knuckle of ER, creates a promiscuous ER that is able to bind to GRE/PREs by contacting this thymine. Elements with the sequence GGTCAcagTGTYCT that represent hybrids between an estrogen response element and a GRE/PRE respond to estrogens, glucocorticoids, and progestins in vivo and bind all three wild-type receptors in vitro. These hybrid HREs could serve to confer promiscuous gene regulation.